Association between health insurance enrolment and maternal health care service utilization among women in Ethiopia - Abdu Seid; Mohammed Ahmed (BMC, 2021)
Abstract Background Health insurance was considered as the third global health transition which can increase access to health care services by eliminating monetary obstacles to maternal health care use, particularly in emerging nations. Hence, this study aimed to assess the association between health insurance enrolment and maternal health care service utilization among women in Ethiopia. Methods A cross-sectional study was conducted using the 2016 Ethiopia Demographic and Health Survey (EDHS) data set. About 4278 mothers who had delivered at least one child in the last five years of the survey were selected in the study. Multivariate logistic regression analysis was performed to measure the relationship between health insurance enrolment and maternal health care service utilization by controlling confounders An adjusted odds ratio with a 95% confidence interval and p-values < 0.05 were well-thought-out to state the imperative association. Results The overall health insurance coverage among the women was 4.7%. About, 18.1% of women from households in the poorest wealth quantile had no health insurance coverage for maternal health care services. Moreover, 84% of women lived in a rural area did not enclose by health insurance. According to multivariate logistic regression, the likelihoods of ANC utilization were 1.54 times (AOR: 1.54; 95% CI: 1.06-2.25) higher among mothers who were enrolled in health insurance compared to their counterparts. In the same vein, the likelihoods of been attended by a skilled birth attendant were 1.84 times (AOR: 1.84; 95% CI: 1.1-3.08) higher among mothers who were enrolled in health insurance. Conclusions This study has shown that women enrolled in health insurance were associated with skilled delivery and recommended ANC utilization than women who did not enroll in health insurance. Health insurance enrolment enterprises must be available to all pregnant women, particularly those of poorer socioeconomic rank.